Mahākavi G̲ẖāliba - Hr̥daya, Vyathita (Rashṭrabhāsha Prakāśana, 1984)
Life and times of Mirza Asadullah Khan Ghalib ; accompanied by a representative selection of his Persian and Urdu poetry rendered in Devanagari transliteration.